Tolerance of Cabbage Crop to Auxin Herbicides - NASCIMENTO,A.L.V. (2020)
ABSTRACT: The presence of weeds in cabbage cultivation areas causes a reduction in the productivity and quality of the commercial product. Given the difficulties in management and the scarcity of registered products for weed control in cabbage cultivation, this study aimed to evaluate the tolerance of the cabbage cultivars Astrus Plus to the herbicides 2,4-D and dicamba. Two experiments were performed; one under controlled conditions and another conducted in the field. The efficacy of the herbicides on the initial growth of the crop was evaluated in the first experiment, measuring the dry matter of the aerial part, the root of the plant, and evaluating the intoxication of the plants. Plant poisoning was also evaluated in the second experiment, along with crop production. No changes in the dry matter and plant poisoning were observed after the analyses performed in the controlled environment, showing that the cabbage presented tolerance to the applied herbicides. On the other hand, results from the experiments performed in the field showed that herbicide 2,4-D poisoned the cabbage causing reductions in production. Dicamba did not cause any damage in the initial phase of cultivation to this crop, with no reductions in its production. These results indicated the potential use of this herbicide in cabbage cultivation. It can be concluded from this study that the cultivar Astrus Plus is tolerant to dicamba. Under controlled conditions, 2,4-D does not cause toxicity to this cultivar, different from its effect when used in the field, where this herbicide can kill the cabbage plants.